Adsorption characteristics of [Fe(III)–EDTA]− on granular activated carbon from aqueous solutions. Issue 3 (19th April 2012) - Yang, Xiao‐Juan; Long, Xiang‐Li; Yuan, Wei‐Kang
<x xml:space="preserve">Abstract</x> In this study, the adsorption of [Fe(III)–EDTA]− on coconut‐activated carbon from aqueous solutions has been studied in a batch stirred cell. Experiments have been carried out to investigate the effects of temperature, [Fe(III)–EDTA]− concentration, pH, and activated carbon mass on [Fe(III)–EDTA]− adsorption. The experimental results manifest that high temperature is favorable to the adsorption of [Fe(III)–EDTA]− on the activated carbon. The [Fe(III)–EDTA]− adsorption on activated carbon increases with its concentration in the aqueous solutions. However, the [Fe(III)–EDTA]− adsorption on activated carbon decreases as the pH rises. The [Fe(III)–EDTA]− adsorption on per gram of activated carbon decreases as the activated carbon mass increases. The kinetic study shows that [Fe(III)–EDTA]− adsorption on the activated carbon is in good compliance with the pseudo‐second‐order kinetic model. The Langmuir and Freundlich equilibrium isotherm models are found to provide a good fitting of the adsorption data. Thermodynamic parameters such as Ea, ΔG0, ΔH0, and ΔS0 for adsorption reaction are estimated. © 2012 American Institute of Chemical Engineers Environ Prog, 32: 470–479, 2013